Uji Antibakteri Ekstrak Rimpang Koenih Rimbo (Curcuma sumatrana Miq.) Tumbuhan Endemik Sumatra Barat terhadap Bakteri Gram Positif - Feskaharny Alamsjah; Anthoni Agustien; Tri Widia Ningsih Alam (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Koenih rimbo (Curcuma sumatrana Miq.) is a medicinal plant endemic to Sumatra from the Zingiberaceae family. Research on the antibacterial test of koenih rimbo rhizome extracts against Gram-positive bacteria has been conducted at the Basic Biology Laboratory, UPT. Basic and Central Laboratory, Chemical Laboratory of Natural Materials, UPT. Biological Resources, Andalas University,Padang. This study aims to determine the antibacterial activity of fresh extracts, infusions, and ethanol extracts and determine the largest inhibition zone of koenih rimbo rhizomes against several Gram-positive bacteria. The research used a survey method with a purposive sampling technique. The results showed that the fresh extract, infusa, and ethanol extract had antibacterial activity against Gram-positive bacteria (Staphylococcus aureus, S. epidermidis, Bacillus subtilis, and B. cereus. The most significant inhibition zone was obtained from the extract with ethanol solvent with a strong inhibition category.